Komposisi Spesies dan Struktur Komunitas Moluska Bentik Teluk Jakarta - Hendrik A.W. Cappenberg (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The Composition of Species and Structure of Benthic Mollusc of Jakarta Bay. The development and increasing of population in mainland may have negative impact on water and sediment quality in the Jakarta Bay as habitat of benthic molluscs. The study was conducted in June and September 2003. The aim of this study was to observe the species composition and diversity of benthic mollusc community in the Jakarta Bay. Samples were collected from 30 stations at 1 – 12 m depth using Smith McIntyre Grab with opening area was 0.05 m². A sieve with 0.5 mm in mesh size used for collecting benthic molluscs as well as for determining the profil of benthic substrates. Results of this study showed that the substrate in the study sites was characterized by muddy, muddy sand and sandy mud sediment. A total of 24 mollusc species were identified, which belong to 18 genera. Abundance of benthic molluscs ranged from 0.3 to 15779.7 individu/m2 in June and from 0.3 to 820.3 individu/m2 in September. Tellinidae was the highest species composition, and Alveinus sp. (Kelliellidae) was distributed widely in June and September. Most of the molluscs found in this study area were common species in Indonesia waters. The value of diversity index (H’) ranged from 0.03 to 0.95 and evenness index (J’) ranged from 0.05 to 0.69 in June and in September diversity index (H’) ranged from 0.01 to 1.08 and evenness index (J’) ranged from 0.01 to 1.00. These indexes showed that the diversity of benthic mollusc in Jakarta Bay were relatively low.